Effect of an enzyme-containing mouthwash on the dental biofilm and salivary microbiome in patients with fixed orthodontic appliances: a randomized placebo-controlled pilot trial - Hoffstedt, Tove; Skov Hansen, Lea Benedicte; Twetman, Svante; Sonesson, Mikael (European journal of orthodontics, 2023)
Mouthwashes containing oral antiseptics or enzymes are suggested suitable for controlling biofilm accumulation in patients with fixed appliances and thereby limiting unwanted side effects during the orthodontic treatment. To evaluate the effect of an enzyme-based mouthwash on the amount of dental biofilm and the composition of the salivary microbiome in patients undergoing treatment with fixed orthodontic appliances. Randomized double-blind placebo-controlled trial. In total, 35 young adolescents (14-18 years) under treatment with fixed appliances were consecutively enrolled and randomly allocated to an experimental or a placebo group by opening a computer-generated numbered envelope. The subjects were instructed to rinse twice daily during an intervention period of 8 days with experimental mouthwash or placebo without active enzymes. Unstimulated whole saliva samples were collected at baseline and after 8 days. The participants and examiner were blinded for the allocation. The primary outcome was the Orthodontic Plaque Index (OPI) and the secondary was the composition of the salivary microbiome. In total, 28 adolescents (21 females and 7 males) completed the trial and there were no differences in age, clinical, or microbial findings between the test (n = 14) and the placebo group (n = 14) at baseline. We found a decreased OPI in the test group after 8 days and the difference was statistically significant compared with the placebo group (P < 0.05). There were no significant treatment effects on the richness and global composition of the salivary microbiome. In total, one participant in the test group claimed nausea and abandoned the project. In total, two participants did not like the taste of the mouthwash but used it as instructed. No other adverse events or side effects were reported. Short-term pilot trials may by nature be sensitive for selection and performance biases and are not designed to unveil persisting effects. Daily use of enzyme-containing mouthwash reduced the amount of dental biofilm in adolescents under treatment with the fixed orthodontic appliances, without affecting the composition of the salivary microbiota. Approved by the Regional Ethical Board, Lund, Sweden (Dnr 2020-05221). NCT05033015.